Características epidemiológicas asociadas a la condición de egreso del paciente con COVID–19 de cuidados críticos de un hospital III 1 Minsa Iquitos 2021 - Panduro Paredes, Maura (2024)
The purpose of the study was to determine the association between the epidemiological characteristics and the discharge condition of the patient with COVID-19 from critical care of a Hospital III 1 MINSA Iquitos 2021. The quantitative method was used with a non-experimental, descriptive, correlational, retrospective design. The population and sample consisted of 258 patients with COVID-19 registered in the medical records. The technique was the documentary review and the instrument: Data recording of epidemiological characteristics and discharge condition of the patient with COVID-19 from critical care. The Chi Square (X2) statistical test was used with a 95% significance level. The results were: 48.1% were between 40 and 50 years old, 59.7% were male, 47.7% had secondary education, 55% were cohabitants, 33.7% had hypertension, 25,2% diabetes, 5.4% obesity, 5.4% chronic kidney disease, 0.4% cancer, 7.4% heart disease, 17.1% other comorbidities, 85.7% required invasive mechanical ventilation, 45,7% had a time of illness greater than 13 days, 36.8% had a time in the critical care unit of 8 to 15 days, 57.8% came from Iquitos, 61.6% came from other services and 61.2% had a discharge condition of death. In conclusion, there is a significant statistical association between the discharge status of the patient with COVID-19, age p = 0.000, sex p = 0.021, level of education p = 0.013, hypertension p = 0.000, diabetes p = 0.000, obesity p = 0.044, chronic kidney disease p = 0.044, heart disease p = 0.002 and others p = 0.000, ventilatory support p = 0.026, illness time p = 0.024, time in the critical care unit p = 0.040. No statistical association was found with marital status p = 0.979, cancer p = 0.728, district of origin p = 0.404 and service of origin p = 0.510.